The grid of indefinite incarceration: Everyday legality and paperwork warfare in Indian-controlled Kashmir. (September 2020) - Ghosh, Shrimoyee Nandini; Duschinski, Haley
This article analyzes the everyday legality of the preventive detention regime in Kashmir as a means of waging war against political dissidents. We follow the circulation of detainees and their files across multiple legal venues and regimes to show how the counterinsurgency state reinscribes spectacular and terrifying forms of violence through modalities of banal paperwork and iterative performances of the rule of law. Drawing on ethnographic and textual interpretation of legal documents, including police dossiers, detention orders, and police complaints, we argue that the permanent emergency in Kashmir operates through an everyday hyperlegality of indefinite incarceration that intermingles the systems, techniques, and jurisdictions of colonial policing, bureaucratic paperwork, and military warfare. Further, we demonstrate how this grid of indefinite detention manifests through a temporality of deferral and delay that comes to characterize everyday life for its subjects.